Fuzzy Regression Models Using the Least-Squares Method based on the Concept of Distance: Simplified Approach - Al-Qudaimi, Abdullah; Yousef, Walid (OICC Press, 2021)
The study presents a simplified approach to fuzzy regression models using the least-squares method based on the concept of distance. It discusses fuzzy linear regression with fuzzy observations and proposes a method that simplifies parameter estimation while retaining the ability to model uncertainty in data.